IDENTIFIKASI BAKTERI DARI LIMBAH CAIR MINYAK BUMI SEBAGAI MODUL PEMBELAJARAN KONSEP PROKARIOT PADA MATA KULIAH MIKROBIOLOGI DASAR - ', Suratni; Sayuti, Irda Sayuti; Wulandari, Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was aimed at studying the identification of bacteria from the liquid waste of petroleum from August to October 2014. The result of research was used to development a learning module in basic microbiology course. This research was implemented in 2 steps, they are Laboratory research and development a learning module by use of ADDIE (Analysis, Design, Development, Implementation and Evaluation) development. Isolation of bacteria was under taken using thinning methods (platting methods) grown at solid media Stone Mineral Salt Solution Extract Yeast (SMSSe) added with crude oil as selective media. Colonies observed on the media after incubation on the temperature 28-300C for 24-48 hours were identified based on macroscopic observations, microscopic and biochemical tests to ensure that the bacteria identified was absolutely petroleum bacteria. The research result carried out 3 genera of bacteria namely Enterobacter, Pseudomonas and Klebsiella. The result of research is developed as learning module in the concept of prokaryot to enrich teaching materials in basic microbiology course. Key words: Identification, SMSSe Media, Learning Module